2011
DOI: 10.1016/j.joca.2010.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceuticals: do they represent a new era in the management of osteoarthritis? – a narrative review from the lessons taken with five products

Abstract: Additional data are needed for most of the studied nutraceuticals. Studies of good quality are needed to draw solid conclusions regarding their efficacy but nutraceuticals could represent good alternates for OA management. Their use should be driven by any recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
113
0
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(126 citation statements)
references
References 117 publications
0
113
0
9
Order By: Relevance
“…Останнім часом застосування похідних колагену широко висвітлюється в наукових публікаціях, проте рекомендації для лікарів ґрунтуються на результатах лише кількох рандомізованих клінічних досліджень і мають рівень доказовості від помірного до низького [2,10]. Тим не менше існує потреба в проведенні подаль-ших робіт, що будуть направлені на пошук вірогідних фактів щодо доцільності та безпечності використання похідних колагену серед пацієнтів з остеартрозом, зо-крема гонартрозом, чому й присвячене наше дослі-дження.…”
Section: îðèã³íàëüí³ äîñë³äAeåííÿ Original Researchesunclassified
“…Останнім часом застосування похідних колагену широко висвітлюється в наукових публікаціях, проте рекомендації для лікарів ґрунтуються на результатах лише кількох рандомізованих клінічних досліджень і мають рівень доказовості від помірного до низького [2,10]. Тим не менше існує потреба в проведенні подаль-ших робіт, що будуть направлені на пошук вірогідних фактів щодо доцільності та безпечності використання похідних колагену серед пацієнтів з остеартрозом, зо-крема гонартрозом, чому й присвячене наше дослі-дження.…”
Section: îðèã³íàëüí³ äîñë³äAeåííÿ Original Researchesunclassified
“…The concentrations of ASU, GLU, CS and PBZ used in the present study were previously reported to have significant anti-inflammatory effects and are clinically relevant [39]- [46]. Cells were then activated for 24 hours with IL-1β (10 ng/mL, R&D Systems, Minneapolis, MN, USA) or lipopolysaccharide (LPS, 1 ng/mL, Sigma-Aldrich).…”
Section: Treatment Designmentioning
confidence: 99%
“…ASU, GLU and CS have been documented to reduce inflammation in vitro [9] [10] [11], [31]- [38], and in vivo [39]- [46]. These agents have been reported to ameliorate OA in man and animals with minimal adverse side effects [39]- [46].…”
Section: Introductionmentioning
confidence: 99%
“…Naime, epidemiološka istraživanja su suboptimalni unos pojedinih nutrijenata povezale sa rizikom za nastanak i razvoj OA (8). Posebno značajan nutritivni aspekt predstavlja racionalna i bezbedna primena sve većeg broja dijetetskih suplemenata u primarnoj i sekundarnoj prevenciji OA (9).…”
Section: Uvodunclassified